2019
DOI: 10.3389/fped.2019.00345
|View full text |Cite
|
Sign up to set email alerts
|

Greater Reduction in Abdominal Than in Upper Arms Subcutaneous Fat in 10- to 12-Year-Old Tennis Players: A Volumetric MRI Study

Abstract: Background: Little is known about the impact of long term participation in sports and subcutaneous fat volume in children. This study aimed at determining whether tennis participation is associated with lower subcutaneous adipose tissue volume (SATv) in the abdominal and upper extremities in children. Methods: Magnetic resonance imaging (MRI) was used to determine the SATv stored in the abdominal region and upper arms in seven tennis players and seven inactive children matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Fourthly, the studies included in our meta-analysis consisted of training programmes lasting 2-20 weeks; longer-term interventions were not addressed. However, on the basis of the current findings and those derived from some cross-sectional studies involving athletes with several years of training using one limb more than the contralateral one (e.g., tennis) [7,35,90], longer-term interventions would probably help to confirm the presented findings.…”
Section: Limitationssupporting
confidence: 73%
“…Fourthly, the studies included in our meta-analysis consisted of training programmes lasting 2-20 weeks; longer-term interventions were not addressed. However, on the basis of the current findings and those derived from some cross-sectional studies involving athletes with several years of training using one limb more than the contralateral one (e.g., tennis) [7,35,90], longer-term interventions would probably help to confirm the presented findings.…”
Section: Limitationssupporting
confidence: 73%
“…This contradicts the study results from a recent study using DXA in which no significant side-to-side difference in fat mass was observed at the upper limb level of elite female tennis players (aged 21 years on average), and greater ipsilateral limb fat mass was found in the lower limb (Chapelle et al, 2020). Also, a study conducted with magnetic resonance imaging (MRI) indicated that the repetitive use of the dominant upper limb does not elicit segmental adaptations in fat mass in this particular limb (Sanchis-Moysi, Serrano-Sanchez, Gonzalez-Henriquez, Calbet, & Dorado, 2019). Therefore, one should be cautious with interpreting these results and more research is needed to confirm our results.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetrical loading in the long term may lead to asymmetry in professional tennis players due to existence of approximately 20% more bone mineral content and muscle mass in the dominant arm [39,40]. It has been reported that long-term tennis playing during childhood is associate with reduced subcutaneous adipose volume, but no significant differences between the arms of 10-to 12-year-old players [41]. On the other hand, non-significant differences of asymmetry (muscle volume) in iliopsoas and gluteal muscles between dominant vs. non-dominant legs were observed in soccer players [42].…”
Section: Segmental Comparison Of Upper and Lower Extremity Muscle Massmentioning
confidence: 99%